Identifikasi Faktor Iklim Kerja, Kebisingan, dan Pencahayaan pada Sektor UMKM Kediri - Syalsya Putri Kumala Sari; Budhi Setianto; Muh. Agus Ainur Rosyid; Oktofa Setia P (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Occupational health and safety is an important aspect that needs to be considered in the company's management system, because it involves activities or activities that protect and maintain the resources or inputs owned by the company such as equipment, facilities and human resources from accidents that can be harmful and detrimental company. UKM Kediri is an association of UMKM, namely UKM Making Tofu, Making Herbal Beverages, Making Crackers, and Self-Service Sales. To run this MSME, each MSME has a way to produce well in different ways. In the production process, UMKM still pays little attention to the physical work environment, specifically in the Working Climate, Noise and Lighting sections. This research is descriptive in nature with a cross-sectional design in this measurement referring to the Minister of Manpower Standard Number 5 of 2018 concerning Occupational Safety. From the results of Identification of Working Climate Factors, Noise, and Lighting in the Kediri MSME Sector that the working climate factors in the cracker oven section and the cracker dough cooking section still exceed the NAB standard. the noise factor in the Soybean Boiling, Tofu Printing, and Herbal Beverage Squeezing Production Sites is close to NAV. the lighting factor in the Production Area for Squeezing Herbal Beverages, the Cracker Printing Area, the Materials Section and the Dough Mixing Container is still insufficient to exceed the NAV. The working climate factor needs to be controlled, the lighting factor is still inadequate, it is necessary to add lighting and noise that exceeds the threshold value, but there are 2 points in the Kediri MSME production process for the need for personal protective equipment (earphones).